2012
DOI: 10.1590/s0102-311x2012001000009
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in health among women in Campinas, São Paulo State, Brazil

Abstract: The aim of this study was to assess social inequalities in health status and use of health services according to level of schooling in women. This was a cross-sectional population-based study with a sample of 508 women from 20 to 59 years of age living in Campinas, São Paulo State, Brazil (ISA-Camp 2008). Women with less schooling showed higher prevalence of hypertension, circulatory problems, headache, dizziness, obesity, common mental disorders, worse self-rated health, use of dental prosthesis, and visual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(50 reference statements)
1
7
0
3
Order By: Relevance
“…This agrees with previous studies that reported socioeconomic inequalities in health in Brazil 13,24,25 . Brazil has major socioeconomic inequalities in health, with the most adverse health outcomes occurring among the poorest segments of the population 4 .…”
Section: Access Use and Quality Of Health Care Services And Trends supporting
confidence: 93%
“…This agrees with previous studies that reported socioeconomic inequalities in health in Brazil 13,24,25 . Brazil has major socioeconomic inequalities in health, with the most adverse health outcomes occurring among the poorest segments of the population 4 .…”
Section: Access Use and Quality Of Health Care Services And Trends supporting
confidence: 93%
“…As the literature points out, there are many social factors involved in the mental health and well-being of women along their lives 18,19 . However, this study concluded that, in all the social determinants of health, some have greater significance than others for women's mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, o nível educacional contribui para a aquisição de informações e adoção de comportamentos saudáveis. Pior condição de saúde, avaliada por meio de vários indicadores nas mulheres com menor nível de escolaridade, já havia sido constatada previamente no mesmo município da presente pesquisa 30 .…”
Section: Resultsunclassified